Divergent aerosolization behaviors of bacteria and fungi shape the pathogen profile of pig manure composting-derived bioaerosols - Xia Gao; Jiani Wang; Lijuan Peng; Tianlong Song; Ruolan Tang; Yan Yang; Guoxue Li; Jing Yuan (Journal of Environmental Chemical Engineering, 2026)

Machine learning based accurate storm surge peak and timing forecast in Pearl River Estuary - Ruolan Xiong; Xiaohui Wang; Fuhai Dao; Hongze Leng; Junqiang Song (Frontiers in Marine Science, 2026)
With climate warming, storm surge increasingly threatens coastal cities, underscoring the necessity for accurate and timely forecasts of peak surge height and timing. Among widely used neural network-based approaches in storm surge forecasting, the Gated Recurrent Unit (GRU), while strong in sequential prediction, tends to underestimate peak magnitudes and exhibits timing errors at extended lead times. To address the issue, this study developed a single-station GRU prediction model using storm surge data from 42 tropical cyclones (2000-2023) at nine stations in the Pearl River Estuary. To reduce peak underestimation, an iterative forecasting scheme was designed, incorporating tropical cyclone (TC) parameters selected via Accumulated Local Effects (ALE) and correlation coefficient. To mitigate peak timing errors, a Support Vector Regression (SVR) model based on TC peak intensity elements was proposed to predict and correct peak timing errors. Additionally, multi-station joint forecasting was explored by embedding spatial information between stations and TC tracks. Results based on leave−one−out cross−validation (LOOCV) indicated that integrating TC location, distance, and 34−kt wind radii in the key quadrants yielded a 27% reduction in Peak Error (PE) at 12–18 h and a 13% reduction in RMSE over 1–18 h for the 35 test cases. After applying the SVR−based phase correction, the forecast for all cases achieved an 55% reduction in Timing Error (TE) and a 2.81% reduction in RMSE relative to the uncorrected forecast. Compared to numerical model outputs, the RMSE of water level sequence during Typhoon Hato was decreased by 0.22 m. Multi-station joint forecast results showed that embedding such spatial information not only enhances forecast skill across multiple gauges but also provides benefits for stations with sparse historical data. This study offers a promising method that targets both the magnitude and timing of storm surge peaks, thereby improving the accuracy and reliability of storm surge forecasting.

Sublethal and lethal exposure to broflanilide disrupt sex pheromone biosynthesis signaling and reproductive success in the Spodoptera frugiperda - Zelong She; Ruolan He; Xianxue Song; Qisheng Song; Jizhen Wei; Mengfang Du; Xinming Yin; Shuangyan Yao; Shiheng An (Pesticide Biochemistry and Physiology, 2026)

Al-doped Ti4O7 with superior oxidation resistance and optical stability for high-temperature solar-thermal applications - Peize Lyu; Wenzhao Sun; Bo Yang; Wanqi Chen; Ruolan Tang; Haile Yan; Zongbin Li; Song Li; Liang Zuo (Chemical Engineering Journal, 2026)

Correlation analysis and modeling application from objective indicators to subjective evaluation of scented tea: A case study of rose tea - Ruolan Song; Meng Shen; Yanran Wang; Youyi Sun; Jiamu Ma; Qingyue Deng; Xueyang Ren; Xianxian Li; Yuan Zheng; Yingyu He; Feng Zhang; Mingxia Li; et al. (Food Chemistry, 2025)

Effects of single or combined exposure to tralopyril and ocean acidification on energy metabolism response and sex development in Pacific oysters (Crassostrea gigas) - Ping Li; Minghao Yin; Xu Wang; Ruolan Jia; Chengzhaung Chen; Bin Liu; Yiwei Liu; Bianhao Zeng; Tengzhou Li; Ling Liu; Hong-Jun Song; Zhi-Hua Li (Marine Pollution Bulletin, 2024)

Rapid and highly sensitive colorimetric LAMP assay and integrated device for visual detection of monkeypox virus - Yadan Peng; Ruolan Hu; Shuang Xue; Yugan He; Lili Tian; Zehan Pang; Yile He; Yuqi Dong; Yinghan Shi; Shuqi Wang; Bixia Hong; Ke Liu; et al. (Analytica Chimica Acta, 2024)

Pickering emulsion stabilized using modified gluten protein - Yongling Song; Yuanyuan Hou; Siqi Ren; Chenling Qu; Miao Li; Yanlin Tu; Ruolan Wang (Journal of Food Engineering, 2024)

Bradykinin-pretreated Human cardiac-specific c-kit+ Cells Enhance Exosomal miR-3059-5p and Promote Angiogenesis Against Hindlimb Ischemia in mice - Jingzhou Li; Fei Song; Ruolan Chen; Jinjuan Yang; Jie Liu; Li Huang; Fuyu Duan; Meng Kou; Boon Xuan Lian; Xiaoxia Zhou; Weimin Han; Liang Mao; et al. (Stem Cell Reviews and Reports, 2023)

Clarifying the effect of gut microbiota on allergic conjunctivitis risk is instrumental for predictive, preventive, and personalized medicine: a Mendelian randomization analysis - Kangcheng Liu; Yingjun Cai; Kun Song; Ruolan Yuan; Jing Zou (EPMA Journal, 2023)

Molecular tracers, mass spectral tracers and oxidation of organic aerosols emitted from cooking and fossil fuel burning sources - Chengrui Liang; Shuxiao Wang; Ruolan Hu; Guanghan Huang; Jinzi Xie; Bin Zhao; Yuyang Li; Wenfei Zhu; Song Guo; Jingkun Jiang; Jiming Hao (Science of The Total Environment, 2023)